Framework for Enhanced Applicability of the Egyptian Public Procurement Law to International Administrative Construction Contracts - Abu Helw, Amr (AUC Knowledge Fountain, 2021)
Local governments and public authorities conclude contracts for the purpose of acquisition of goods, delivery of services and construction of public facilities like bridges, infrastructures and public buildings. A public contract is an agreement to perform particular tasks financed by government funds to the benefit of the whole community. Private entities and corporations are subject to stricter standards in their dealings with the government than in private transactions. Conversely, the government must deal fairly and equitably with those who it contracted with to achieve successful implementation of the projects. On October 3, 2018, a new Egyptian public procurement law, namely, law no. 182 of 2018 was issued to regulate contracts concluded by public authorities. The executive regulation of the law was published on October 31, 2019. After extensive study and review of legislation and standard administrative contracts in selected European counties, Middle Eastern countries and others, this research propose amendments to the Egyptian public procurement law to make it more equitable and to avoid unbalanced provisions that could make international contractors and investors decide to refrain from dealing with major public projects in Egypt. The suggested amendments address five dominant subjects, namely; (i) delay claims by the contractor, (ii) contract termination, (iii) limit of compensation under performance guarantee, (iv) price adjustment and (v) dispute resolution mechanism. To verify the proposed amendments, semi-structured interviews are conducted among four eminent and renowned experts in the field of public work contracts to obtain their opinions and comments. The experts’ recommendations are implemented to make the amendments more comprehensive and better applicable to their intended purpose.